Rethinking Supply Chain Resilience in Strategic Industries: Taiwan’s Semiconductor Sector under Geopolitical Uncertainty - Ashri Ramadhan; Miguel González (PT. Islamic Research Publisher, 2024)
This study examines supply chain resilience strategies within Taiwan’s semiconductor industry amid intensifying geopolitical uncertainties. It explores how the industry manages supply chain vulnerabilities under geopolitical tensions, identifies adaptive strategies that ensure production continuity despite external pressures, and evaluates the implications of production diversification on Taiwan’s long-term technological competitiveness. A mixed-method approach is employed, combining qualitative interviews with industry executives and quantitative analysis of trade flow data to capture both strategic decision-making and structural supply chain dynamics. The findings reveal that Taiwanese semiconductor firms have developed multilayered resilience mechanisms, including geographical diversification of production facilities, advanced strategic inventory management, and the strengthening of international partnership networks that function as buffers against geopolitical disruptions. The study further shows that while production diversification enhances operational security, it also introduces strategic trade-offs, particularly concerning Taiwan’s innovation capacity. Maintaining competitiveness depends not only on risk dispersion but also on preserving high-density innovation clusters that have historically driven technological leadership in the semiconductor sector. Excessive fragmentation of production networks may therefore weaken the ecosystem’s innovative efficiency, despite improving short-term resilience. Academically, this study contributes to the literature on supply chain resilience and geopolitical risk by advancing a context-specific framework for understanding resilience in strategically critical high-tech industries. It integrates insights from international business, strategic management, and operations research to demonstrate that resilience is not merely a function of risk mitigation, but also of ecosystem-level innovation dynamics. Furthermore, it extends existing debates on supply chain diversification by highlighting the tension between geopolitical risk reduction and innovation concentration, offering a nuanced perspective on how firms and nations can balance security, efficiency, and technological leadership in an era of global fragmentation.